Content of Investigative Situations of the Initial Stage of Investigating Coercion to Fulfill or Non-Fulfillment of Civil Obligations Committed by Organized Criminal Groups (Law and Safety, 2020)
A number of issues concerning the essence of the investigative situation have been studied. The author has indicated the need for a comprehensive study of its constituent elements, given the specifics of the investigation of coercion to fulfill or non-fulfillment of civil obligations committed by an organized criminal group. The interrelationships of investigative situations of the initial stage of the investigation have been analyzed; directions of the development have been indicated. The bases for choosing and realizing actions at the initial stage of investigation have been analyzed; investigative situations and algorithms of the corresponding actions have been specified. Ways to solve a difficult situation and transition from one investigative situation to another during the pre-trial investigation have been suggested. Based on the analysis of scientific opinions on such a forensic category as the investigative situation of the initial stage of the pre-trial investigation, the author has substantiated own views on this issue. The processes that take place in the system of interrelation of the investigative situation of the initial stage of the investigation along with the actions corresponding to it have been studied. The specific investigative situations of the initial stage of the pre-trial investigation and the actions that correspond to them during the investigation by the fact of coercion to fulfill or non-fulfillment of civil obligations committed by an organized criminal group have been analyzed.Taking into account the positive and negative practice of investigating crimes related to the researched crime, the author for the first time has elaborated an algorithm of the investigator’s behavior at the initial stage of their investigation, given that those actions are committed by an organized group of people. Given the positive practice of investigating coercion to fulfill or non-fulfillment of civil obligations, the author has defined the possible ways to use information about the investigative situations of the initial stage of the investigation in order to optimize the activities of investigative units during the investigation of this category of criminal proceedings. Typical investigative situations of the initial stage of investigation have been studied and algorithms of the investigator’s actions during their realization have been defined.
Keywords: typical investigative situation; investigative actions; secret investigative search actions; initial stage of investigation; civil obligations; coercion to fulfill or non-fulfillment of civil obligations